2004
DOI: 10.1111/j.1440-1681.2004.04086.x
|View full text |Cite
|
Sign up to set email alerts
|

Role of endogenous macrophage inflammatory protein‐2 in regulating fever induced by bacterial endotoxin in normal and immunosuppressed rats

Abstract: During myelosuppressive chemotherapy, Gram-negative bacterial infection with consequent exposure to lipopolysaccharide (LPS) is one of the most important causes of persistent fever. The classical model of the pathogenesis of fever suggests that pro-inflammatory cytokines, produced by leucocytes in the bloodstream in response to exogenous pyrogens such as bacterial LPS, represent the distal mediators of the febrile response. Neutrophils are the first effectors cells and the most prominent leucocyte population i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
15
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(19 citation statements)
references
References 47 publications
4
15
0
Order By: Relevance
“…That is, the reduction of circulating leukocytes by cyclophosphamide caused significantly enhanced fevers (in both magnitude and duration), and this effect was associated with a significant reduction of circulating inflammatory cytokines compared to those in immunocompetent animals. The present findings confirm previous experimental and clinical studies that show that the production of fever was not dependent on the presence of leukocytes in the peripheral circulation (3,24,28). Furthermore, they suggest that other, yet-to-be identified mediators as possible mechanisms of immune signaling are involved in the development of the acute-phase response to gram-negative and gram-positive infections.…”
Section: Discussionsupporting
confidence: 80%
See 4 more Smart Citations
“…That is, the reduction of circulating leukocytes by cyclophosphamide caused significantly enhanced fevers (in both magnitude and duration), and this effect was associated with a significant reduction of circulating inflammatory cytokines compared to those in immunocompetent animals. The present findings confirm previous experimental and clinical studies that show that the production of fever was not dependent on the presence of leukocytes in the peripheral circulation (3,24,28). Furthermore, they suggest that other, yet-to-be identified mediators as possible mechanisms of immune signaling are involved in the development of the acute-phase response to gram-negative and gram-positive infections.…”
Section: Discussionsupporting
confidence: 80%
“…These results are consistent with the idea that even when cytokines are detected in the blood, their timing does not always correlate with acute-phase activation after administration of immune stimuli (19). Concerning the role of administration of cyclophosphamide, it has previously been shown that this immunosuppressive drug induces a nonspecific leukopenia (fewer than 100 cells/ml for 6 to 7 days) (24,26) and a selective depletion of the lymphoid tissue (2,42). When such treated patients become afflicted with a bacterial infection, they develop high fevers.…”
Section: Discussionsupporting
confidence: 78%
See 3 more Smart Citations